Structure-guided discovery of protein and glycan components in native mastigonemes - Huang, Junhao; Tao, Hui; Chen, Jikun; Shen, Yang; Lei, Jianlin; Pan, Junmin; Yan, Chuangye; Yan, Nieng (Cell, 2024)
Mastigonemes, the hair-like lateral appendages lining cilia or flagella, participate in mechanosensation and cellular motion, but their constituents and structure have remained unclear. Here, we report the cryo-EM structure of native mastigonemes isolated from Chlamydomonas at 3.0 Å resolution. The long stem assembles as a super spiral, with each helical turn comprising four pairs of anti-parallel mastigoneme-like protein 1 (Mst1). A large array of arabinoglycans, which represents a common class of glycosylation in plants and algae, is resolved surrounding the type II poly-hydroxyproline (Hyp) helix in Mst1. The EM map unveils a mastigoneme axial protein (Mstax) that is rich in heavily glycosylated Hyp and contains a PKD2-like transmembrane domain (TMD). Mstax, with nearly 8,000 residues spanning from the intracellular region to the distal end of the mastigoneme, provides the framework for Mst1 assembly. Our study provides insights into the complexity of protein and glycan interactions in native bio-architectures. [Display omitted] •A large number of arabinoglycans are seen in the intact structure of mastigoneme•Well-ordered glycans, mostly linked to hydroxyproline, mediate mastigoneme assembly•Mstax, a large glycoprotein, is the central shaft spanning the entire mastigoneme•Mstax contains a PKD2-like domain that may bind PKD2 High-resolution cryo-EM structure of the intact Chlamydomonas mastigoneme reveals an axial protein Mstax, which serves as the central shaft of a mastigoneme and potentially interacts with PKD2 through its transmembrane domain, and a large array of well-resolved arabinoglycans that mediate the intra- and intermolecular interactions of Mstax and the known component Mst1.